2015
DOI: 10.1038/ng.3434
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association analyses implicate aberrant regulation of innate and adaptive immunity genes in the pathogenesis of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE; OMIM 152700) is a genetically complex autoimmune disease characterized by loss of immune tolerance to nuclear and cell surface antigens. Previous genome-wide association studies (GWAS) had modest sample sizes, reducing their scope and reliability. Our study comprised 7,219 cases and 15,991 controls of European ancestry: a new GWAS, meta-analysis with a published GWAS and a replication study. We have mapped 43 susceptibility loci, including 10 novel associations. Assisted by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
751
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 830 publications
(772 citation statements)
references
References 76 publications
18
751
1
2
Order By: Relevance
“…We also found cluster-specific expression of several poorly annotated SLE susceptibility genes, including WDFY4, CXorf21, and TMEM39A. Interestingly, many of the SLE GWAS genes are transcription factors, supporting the notion that aberrantly regulated gene expression networks in multiple cell types contribute to SLE 38 . Our analysis identified both innate and adaptive immune cell subsets in which these transcription factors (ARID5B, CIITA, ETS, IKZF1, IKZF2, IRF7, IRF8 and PRDM1) are expressed.…”
Section: Cluster-specific Expression Of Genes Associated With Diseasementioning
confidence: 51%
“…We also found cluster-specific expression of several poorly annotated SLE susceptibility genes, including WDFY4, CXorf21, and TMEM39A. Interestingly, many of the SLE GWAS genes are transcription factors, supporting the notion that aberrantly regulated gene expression networks in multiple cell types contribute to SLE 38 . Our analysis identified both innate and adaptive immune cell subsets in which these transcription factors (ARID5B, CIITA, ETS, IKZF1, IKZF2, IRF7, IRF8 and PRDM1) are expressed.…”
Section: Cluster-specific Expression Of Genes Associated With Diseasementioning
confidence: 51%
“…Additionally, we uncovered several novel loci that either fell just below genome-wide significance (P < 5Â10 À8 ) or were not independently replicated. In this follow-up study, we augmented our previous data with an additional cohort from Hong Kong and performed in silico replication together with published cohorts of European and Chinese descent (4,5). The added statistical power of the meta-analysis with nine cohorts allowed us to independently replicate five candidate loci above genome-wide significance.…”
Section: Introductionmentioning
confidence: 99%
“…Disease severity, morbidity and mortality are highest in individuals of non-European descent (1). To date, more than ten genome-wide association studies (GWAS) and historical candidate gene studies have identified diverse risk loci (2)(3)(4). However, these SLE candidate genes taken together are insufficient to explain the entire heritability of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…13, 2017; enriched for ceQTLs but not for reQTLs. Most notably, systemic lupus erythematosus (SLE) GWAS signals 19 were very strongly and significantly enriched among reQTLs with no enrichment in ceQTLs, suggesting that innate immune response to pathogens may be a particularly important environmental modifier of genetic predisposition to SLE, while playing a smaller role in the genetic architecture of e.g.…”
mentioning
confidence: 99%